Advancement of Megadunes and its Implications in the Badain Jaran Sand Sea - Dong, Peng; Liang, Aimin; Zhou, Yali (Frontiers in Earth Science, 2022)
The tallest megadunes on the Earth are developed in China’s Badain Jaran Sand Sea, as a result of which a prolonged curiosity exists with regards to the existence and migration of such large dunes. However, our present understanding of movement of aeolian bedforms is largely limited to dunes with height ranging from several to several tens of meters. Difficulties in understanding the movement of megadunes predominantly exists in the monitoring methods. This study presents the evidence of the megadune advancement and its rate in the Badain Jaran Sand Sea, estimated by optically stimulated luminescence (OSL) dating of sediments on the slipfaces of several megadunes. It is suggested that megadunes experience similar advancement as the commonly observed sand dunes; the rate of advancement of megadunes fits the rate-height relationship. The rate of advancement varies linearly with the reciprocal of megadune height, which has been confirmed for dunes, extending the advancement rate-height relationship to a previously blind range of dune size. In addition, the advancement rate of megadunes exhibits far-reaching implications for megadune formation. In combination with other morphometric evidences, it exemplifies the assumption that the development of megadunes is predominantly controlled by wind rather than other factors such as the underlying relief and ground water, as accepted by most researchers.